In-situ FT-IR spectroelectrochemical identification of processes at solid electrodes - Švegl, Franc; Orel, Boris; Kaučič, Venflorineslav; Kalcher, Kurt (Univerzita Pardubice, 1997)
External reflection FT-IR spectroscopy was used for the elucidation of oxide thin film electrodes. The in-sítu FT-IR spectroelectrochemical measurements allowed direct monitoring of the electrode processes without removing the electrode from the electrochemical environment. A FT-IR spectroelectrochemical cell was designed, which allowed easy exchange and adjustment of the working electrode. Intercalation and deintercalation processes of Li+ ions from an aprotic electrolyte in and out of the layered Li0.99Co1.01O2 oxide thin film on Pt substrate, were investigated by in-situ subtractive normalized interfacial FT-IR technique (SNIFTIR). The reflection-absorption FT-IR spectra were obtained at potentiodynamic conditions at various electrode potentials ranging from −1.0 V to +1.4 V vs. a modified Ag/AgCl. Investigation of a Li0.99Co1.01O2 oxide thin film deposited on Pt substrate showed that in deintercalation/intercalation processes of Li ions reversible structural and electronic changes in the electrode material appeared.